Performance analysis of parametric estimation for indoor localization applications - Lou, Ting Ting (2015)
This report evaluate on the study of the channel parameters, channel transmission line, channel measurements in the frequency domain of 2GHz to 3GHz, and performance analysis for channel measurements within the infinitus laboratory. This experiment measurement consists of antenna choosing, connection of coaxial cable making for transmission line, calibration for the Agilent PNA-X Network Analyzer N5244A (VNA), and performance analysis. And this measurement is to collect channel transfer functions at the laboratory to stimulate the Line-Of-Sight configuration. The testing of bi-conical antenna is conducted by measuring its return power loss and the radiation pattern by applying the theory of S parameter and the polarization. The purpose of the experiment also includes the collective data which is constructed by the time domain response and the power delay profiles of the channels. In this project, an Agilent PNA-X Network Analyzer N5244A (VNA) to perform a localisation sweep with the power level is recorded for studies. Based on the result, of the analysis of the channel parameters, the presence of direct Line-Of-Sight path will produce a lot of multipath delay at the receiver side. This is been address as the power delay profile in the time domain.